STATUS PERLINDUNGAN TUMBUHAN EKSOTIS DAN SATWA LIAR DI CAGAR ALAM LIFMATOLA-WAISAKAI, KEPULAUAN SULA - Widyantoro, Arief; Samurwat, Wahyu; Religa, Alma Salim (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
The utilization of wildlife animals and exotic plants in Indonesia is carried out by species diversity and ecosystem balance in their natural habitat. Nowadays, a lot of plant and animal tradings cause the population descending and animals extinction in wildlife. Natural protection and preservation was aimed to maintaining the uniqueness of wildlife animals and exotic plants which are regulated by nature reserve and distributed by quarantine measures at the entry and exit points in seaports and airports. The research was aimed to study the species and protection status of animals and exotic plants in Lifmatola-Waisakai Nature Reserve, Sula Islands, North Maluku. The research design was descriptive-explorative method using Trend Model Time Series that calculated by Acceptance of Plant and Animal Reports. The study showed that 74 birds, 52 rumps of exotic orchids, 15 woods of Meranti, 9 lizards and 2 Timor deer were found during a period of three years of quarantine measures. The majority of wildlife animals and exotic plants with conservation status are protected by law. There were 6 species that had been circulated between the islands i.e Grammatophyllum scriptum, Cymbidium sp., Cacatua alba, Lorius garrulous, Cervus timorensis and Varanus indicus.